Boundary Regularization of Urban Buildings using Mask Region Convolutional Neural Networks - Vasavi , S.; Krishna , P. V. Sai; Sri , P. D. L. Nikhita (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Knowing the shape patterns can be highly helpful for building extraction in very high-resolution satellite (VHRS) images, which is among the most fascinating and difficult topics. For a variety of purposes, including land-cover mapping, managing urban resources, keeping track of natural disasters, and locating illegal structures. Deep-learning-based semantic segmentation networks have significantly improved building footprint generation performance when compared to more traditional processes. Some of the existing methods like CLP-CNN, and RegGAN have disadvantages that are unavoidably impacted by a number of circumstances, such as unpredictable backgrounds, blurry buildings in the background, obstructions, etc. These methods can utilize local texture and context data, but they are unable to record patterns of building shapes. A solution based on deep learning is suggested to regularize building borders in order to overcome this problem. The Mask R-CNN technique is employed for detection and Masking. For boundary regularization of buildings Guided filter is used to refine the output masks. These refined masks of two images at different timelines are used to perform change detection. This method has given the regularized building footprints as the output in the form of masks with the changes detected. The performance of the proposed system is measured and obtained an accuracy of 0.92, F1-score of 0.95, precision score of 0.93 and recall score of 0.98. By incorporating guided filters for boundary regularization and change detection, the proposed method achieves high precision in detecting building changes and offers a versatile, non-intrusive solution for various applications, including land-cover mapping and urban resource management